2020
DOI: 10.1364/oe.391080
|View full text |Cite
|
Sign up to set email alerts
|

Design, fabrication and characterization of a distributed Bragg reflector for reducing the étendue of a wavelength converting system

Abstract: In this work, the design, fabrication and characterization are reported for a distributed Bragg reflector (DBR) filter with a specific wavelength and angular dependency, which aims to improve the light collection from a wavelength-converter-based light source into a smaller angle than the full angle Lambertian emission. The desired design is obtained by optimizing the transmission characteristics of a multi-layer structure. Titania (TiO 2 ) and silica (SiO 2 ) are used as high and low refractive index material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…A classical thin-film Bragg reflector design consists of a so-called quarter-wave stack of alternating high- and low-index layers, where all layers are of the same optical path length , with the intended photonic stop band’s center wavelength [ 64 , 65 ]. The corresponding reflectance R at the center wavelength , under normal incidence, is approximately given by where is refractive index of the substrate, is the refractive index of the incident (ambient) region, and N is the number of repeating layers.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…A classical thin-film Bragg reflector design consists of a so-called quarter-wave stack of alternating high- and low-index layers, where all layers are of the same optical path length , with the intended photonic stop band’s center wavelength [ 64 , 65 ]. The corresponding reflectance R at the center wavelength , under normal incidence, is approximately given by where is refractive index of the substrate, is the refractive index of the incident (ambient) region, and N is the number of repeating layers.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…At the same time, the peaks become more intensive and symmetrical (Figure 3). It is well known that the intensity of resonant peaks is optimized by increasing both the number of periods and the refractive index contrast between the low and high refractive index segments (∆n) [30][31][32][33]. Since in this case the number of pairs is constant (20-cycle processes), it can be concluded that lower transmittance is caused by the enhancement of the latter parameter.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of geometries, including Bragg reflectors, slabs, opals, microcavities, and colloids, can be used to construct PC structures. One-dimensional PCs, with one direction of periodicity, also known as Bragg stacks/reflectors, are used in antireflective coatings on glass and other optical surfaces [ 38 , 94 , 95 ].…”
Section: Synergizing Fluorescence and Pcsmentioning
confidence: 99%
“…( d ) Example structure of 1D PC slab with an alternating grating of high and low reflective index, adapted with permission from [ 38 ]. ( e ) Example emission of the guided emission from a distributed Bragg reflector (DBR) versus a non-optically active material, adapted with permission from [ 95 ].…”
Section: Figurementioning
confidence: 99%